A Review on Mechanism and Influencing Factors of Shear Performance of UHPC Beams - Weijie Jin; Qiuwei Yang; Xi Peng; Bin Xu (Buildings)
Ultra-High-Performance Concrete (UHPC) is increasingly used in various engineering projects due to its exceptional mechanical properties. This work conducts a literature review of research on the shear performance of UHPC beams in recent decades, with a focus on summarizing the formulas for calculating shear capacity and the main factors influencing shear performance. Firstly, this work reviews the calculation methods for the shear capacity of UHPC beams in different countries, along with their respective advantages and limitations. Subsequently, it provides a detailed analysis of various factors influencing the shear performance of UHPC beams, including longitudinal and stirrup reinforcement, steel fiber content, aggregates, admixtures, the shear-span ratio, shear keys, bolts, shear-reinforcement techniques, and environmental impacts. Through horizontal comparisons, the performance of UHPC beams and ordinary concrete beams under similar experimental conditions is examined to reveal the optimal shear working conditions for UHPC beams. Additionally, it is found that UHPC performs exceptionally well in composite beams, being compatible with numerous materials and significantly enhancing the shear strength of these beams. Lastly, the paper proposes suggestions for maximizing the shear performance of UHPC beams within a safe and reliable operating range and outlines future research directions.